The Influence of Price and Instagram Social Media on Service Use Decisions on CV Reel Seven Organizer Palembang - Panggabean, Angga Putra; Jumjuma, Jumjuma (CV. Civiliza Publishing, 2025)
The development of the tourism industry, especially the MICE (Meeting, Incentive, Convention, and Exhibition) sector, has encouraged the growth of the Event Organizer (EO) business in various cities, including Palembang. CV Reel Seven Organizer Palembang is one of the EO service providers in Palembang which has experienced a significant decrease in the number of events held over the past three years. This study aims to analyze the influence of price and Instagram social media on the decision to use services on CV Reel Seven Organizer Palembang. The method used is quantitative with a survey approach, where data is collected through a questionnaire of 63 respondents who are clients of service users in 2024. The analysis technique used was multiple linear regression with classical assumption test, validity, reliability test, and hypothesis test (t-test and F-test). The results of the study show that the price variables and Instagram social media partially or simultaneously have a positive and significant effect on the decision to use the service. The price variable has a more dominant influence with a regression coefficient of 0.776 compared to social media with a coefficient of 0.344. The results of the determination coefficient (R²) test showed that price and social media were able to influence the client's decision to use the services of CV Reel Seven Organizer Palembang by 85.8%, while the remaining 14.2% was explained by other factors that were not studied in this study. These findings confirm that a competitive pricing strategy and optimal use of Instagram social media can increase consumer interest and decision in using event organizer services. This research is expected to be a strategic input for CV Reel Seven Organizer to increase competitiveness through price adjustments and effective management of Instagram social media.